Simulasi Profil Muka Air Banjir Sungai Petai Di Kota Bangkinang - Riandi, Daly; Fauzi, Manyuk; Sujatmoko, Bambang (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Petai River is the main channel that drains water from most of the drainage in Bangkinang City to Kampar River. The current channel capacity is considered insufficient to drain water, due to frequent flood events occurring at some points of the Petai River. The purpose of this study is to simulate the flood discharge in the existing Petai River cross section, using 10 years return period of flood design. The results of the flood water simulation in HEC-RAS show flooding in Petai 1 and Petai 2 Rivers, but there is no overflow on Petai River 3. Keywords : Petai River, flood, water surface simulation, HEC-RAS,